False flat : why Dutch design is so good. - Betsky, Aaron, 1958-; Eeuwens, Adam, ....- (London : Phaidon, 2004)
The Netherlands is currently one of the world's poles of great modern design; a center of innovation and experimentation in architecture, urban planning, industrial design, and graphic design. From the High Modernist structures designed by Rem Koolhaas and his followers to the rubber buildings and grass-covered libraries designed by younger generations of architects; from the luscious graphic images of Irma Boom to the club-inspired graphics of Dept. and 75B; and from the slick trains and public furniture of BRS Premsela to the recycled chairs and witty assemblies of the designers associated with Droog Design, the range of design is immense, and an inspiration for designers around the world. Yet the work shares a commitment to the ideals of high modernism tempered by the knowledge that these essentially utopian forms will make their appearance in the arena of popular culture. Re-using ideas and materials within the framework of the abstractions and technological streamlining of modernism
Dutch designers approach their work with high purpose and wit. This book presents the dynamism of Dutch design, its particularities and specificity as a manifestation of things intrinsically "Dutch." Eschewing a traditional academic presentation, authors Aaron Betsky and Adam Eeuwens, with the renowned Dutch book designer Irma Boom have conceived a multidimensional structure for the book that brings to life a wealthy design culture in a rich landscape of interconnected stories. False Flat is what one experiences on a bicycle in the Netherlands when the landscape appears to be completely flat, but actually slopes up ever so slightly. The introduction to Betsky's text is a virtual bicycle ride through Rotterdam, a typical Dutch landscape - forged entirely by man. As Betsky points out, the Netherlands is a country that invented itself. The Dutch made their country physically, fighting back the sea and the rivers to make land. Betsky's bicycle ride guides the reader through the man-made countryside
Illustrating the long historical tradition of urban planning in the Netherlands. Betsky's main text gives a thorough overview and insight into the historical, political, social, esthetic, and cultural factors that have led Dutch design to become so highly regarded in the world. Basing their achievements in design on four centuries of tradition, but honed by their engagement with "global culture", the Dutch present us with a design that is witty, "just enough" rather than "almost nothing," and sometimes so "normal" that it reaches the boundary of the ordinary, or even ugly. The work included in this book ranges from that of established architectural firm MVRDV, to young product and graphic designers such as Joep van Lieshout and Thonik. The text is complemented by a wealth of visual material, selected by Eeuwens, which not only illustrates the text, but goes beyond, bringing to life the diversity and often anecdotal quality of Dutch design.
Keywords: Industriële vormgeving